Orbital magnetoresistance in the antiferromagnet CoO driven by dynamic orbital angular momentum - Christin Schmitt; Sachin Krishnia; Mahmoud Zeer; Edgar Galíndez-Ruales; Mehak Loyal; Jonas Köhler; Luca Micus; Takashi Kikkawa; Hiroki Arisawa; Thibaud Denneulin; András Kovács; Renyou Xu; et al. (Science, 2026)
Recent predictions of orders of magnitude larger orbital current effects compared with spin currents have attracted considerable interest. However, orbital currents must first be converted into spin currents to interact with the static magnetization dominated by spin angular momentum in conventional magnets. By using a magnet dominated by orbital angular momentum (OAM), we demonstrate a 70-fold enhancement in orbital Hall magnetoresistance in cobalt II oxide/copper (CoO/Cu*), compared with spin Hall magnetoresistance in cobalt II oxide/platinum (CoO/Pt). This arises from interactions between dynamic OAM from surface-oxidized Cu* and static OAM in the antiferromagnetic insulator CoO. Our results show how by using OAM-dominated materials, we can harness the benefits of giant orbital currents that have not been possible using conventional spin-dominated magnets.